2010
DOI: 10.1111/j.1469-8137.2010.03513.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel mitochondrial protein, short postembryonic roots 1 (SPR1), involved in root development and iron homeostasis in Oryza sativa

Abstract: Summary• A rice mutant, Oryza sativa short postembryonic roots 1 (Osspr1), has been characterized. It has short postembryonic roots, including adventitious and lateral roots, and a lower iron content in its leaves.• OsSPR1 was identified by map-based cloning. It encodes a novel mitochondrial protein with the Armadillo-like repeat domain.• Osspr1 mutants exhibited decreased root cell elongation. The iron content of the mutant shoots was significantly altered compared with that of wild-type shoots. A similar pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 43 publications
(90 reference statements)
2
21
0
3
Order By: Relevance
“…The results showed that the expression of all these genes was upregulated in osabcb14 mutants (Figures a, S4a). These genes were reported to be upregulated under –Fe (Jia et al ., ; Qi et al ., ). Consistent with this finding, qRT‐PCR analysis here showed that all these genes were induced in NIP and osabcb14 mutants under –Fe, but that the induced levels in osabcb14 mutants were significantly lower than in NIP (Figures b, S4b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the expression of all these genes was upregulated in osabcb14 mutants (Figures a, S4a). These genes were reported to be upregulated under –Fe (Jia et al ., ; Qi et al ., ). Consistent with this finding, qRT‐PCR analysis here showed that all these genes were induced in NIP and osabcb14 mutants under –Fe, but that the induced levels in osabcb14 mutants were significantly lower than in NIP (Figures b, S4b).…”
Section: Resultsmentioning
confidence: 99%
“…Rice seedlings grown in hydroponics to 2 weeks of age and peeled rice seeds were analyzed to determine their metal ion concentrations with inductively coupled plasma mass spectrometry (Agilent 7500ce; Agilent Technologies, http://www.home.agi lent.com), as previously described (Jia et al, 2011). Five biological replicates were performed for each sample.…”
Section: Metal Ion Concentrations Assaymentioning
confidence: 99%
“…The EMS-mutated mutant library was generated using the indica rice cv Kasalath (Kas, as described previously in Jia et al (2011), and then screened for mutants with abnormal crown root development. The lcrn1 Kas mutant was isolated and crossed with a japonica rice cultivar, Hei Jing2 (HJ2), with a shorter growth period.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…To date, four short-root genes, OsGNA1, GLR3.1, OsCyt-inv1 and SPR1 have been cloned [11][12][13][14]. osgna1, a rice mutant generated from T-DNA insertion, has a short seminal root, adventitious roots and root hairs when grown at a low temperature (25°C).…”
mentioning
confidence: 99%
“…The length of lateral roots in 7-d-old seedlings of the osspr1 mutant is only 12% of that of the wild type. The OsSPR1 gene encodes a novel mitochondrial protein with an Armadillo-like repeat domain involved in iron homeostasis in rice [14].…”
mentioning
confidence: 99%